VD_FINDINFO HC / 2013 / 567 vom 6. August 2013 - VD Tribunal cantonal (2013)
NOUVEAU MOYEN DE PREUVE, SUSPENSION DE LA PROCÉDURE | 170 al. 2 CPC, 4 al. 1 CPC, 4 al. 2 CPC, 126 al. 1 CPC (CH), 317 CPC (CH), 405 al. 1 CPC (CH)